Importance of Abdominal Ultrasound in 17 Patients with Histologically Confirmed Autoimmune Pancreatitis (AIP) - Mauch, M.; Blank, W.; Kunze, G.; Dirks, K.; Schuler, A.; Klinggräff von, G.; Seitz, K. (Ultraschall in der Medizin - European Journal of Ultrasound, 2015)
Purpose: Autoimmune pancreatitis (AIP) is an independent, underdiagnosed, rare form of chronic pancreatitis. The goal of this study is to document ultrasound findings in histologically confirmed AIP in order to determine the diagnostic value of ultrasound. Materials and Methods: 6 of 74 DEGUM instructors for internal medicine (level 3 and 2) provided anonymized clinical and sonographic data from 17 patients with histologically confirmed AIP.Results: 9/17 patients had diffuse AIP, 8/17 had focal AIP, 14/17 suffered from upper abdominal pain, 9/17 had jaundice, and 3/9 had an elevated IgG4 level. Ultrasound showed diffuse hypoechoic organ enlargement in 9/17 cases and a hypoechoic tumor with an unclear border in 8/17 cases. AIP was verified by ultrasound-guided percutaneous core biopsy in 14 cases, by biopsy of the bile duct in 1 case, and by surgical biopsy in 2 cases. Involvement of the hepatobiliary system was present in 7/17 patients and autoimmune cholangitis was verified in 5 cases. All patients experienced remission after immunosuppressive treatment. The pancreatic duct had a normal width in 11 cases, was dilated in 5 cases, and was stenosed over a long stretch in 3 cases. Contrast-enhanced ultrasound did not show uniform signal increase but also no significantly reduced or absent perfusion. Conclusion: Ultrasound can be diagnostically useful if the clinical manifestations of AIP are known. While the diffuse form allows an ad-hoc suspected diagnosis, the focal form can only be suspected in the case of additional extrapancreatic involvement. Contrast-enhanced ultrasound (CEUS) contributes greatly to the differentiation from ductal adenocarcinoma in the case of focal AIP.
Keywords: autoimmune pancreatitis; pancreas; bile ducts; ultrasound; CEUS